2018
DOI: 10.3389/fonc.2018.00605
|View full text |Cite
|
Sign up to set email alerts
|

Topical Timolol Vs. Oral Propranolol for the Treatment of Superficial Infantile Hemangiomas

Abstract: Objective: Infantile hemangiomas (IHs) are the most common vascular tumors of infancy. Oral propranolol has achieved great success in treating IHs since 2008. To minimize the systemic side events caused by oral administration of propranolol, topical timolol started to be applied in the treatment of IHs, especially for superficial lesions.Methods: We treated 724 children with superficial IHs using oral propranolol or topical timolol, and investigated the efficacy and safety of the two treatment patterns.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 36 publications
7
46
0
1
Order By: Relevance
“…In total, 4730 studies were identified initially after the literature search, of which 20 studies met the inclusion criteria in this meta‐analysis (after duplicates removed) . The selection process is shown in Figure , and the characteristics of the included reports are indicated in Tables and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 4730 studies were identified initially after the literature search, of which 20 studies met the inclusion criteria in this meta‐analysis (after duplicates removed) . The selection process is shown in Figure , and the characteristics of the included reports are indicated in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 4730 studies were identified initially after the literature search, of which 20 studies met the inclusion criteria in this meta-analysis (after duplicates removed). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The selection process is shown in…”
Section: Study Selectionmentioning
confidence: 99%
“…У мультицентричному когортному дослідженні доведено, що використання тімололу для лікування поверхневих ІГ має хороший клінічний ефект і добру переносимість [53]. Водночас, при порівнянні терапевтичного ефекту перорального застосування пропранололу і топічного використання ті-мололу в дітей із поверхневими ІГ виявлено однакові результати [68]. На сьогодні не існує загальноприйнятих схем лікування ІГ із використанням топічних E-блокаторів, проте, якщо буде дов ед е н а е ф е к т и в н і с т ь т а б е з п е ч н і с т ь ї х використання, то топічні E-блокатори можуть стати препаратами «першої лінії» в лікуванні невеликих і поверхневих ІГ, локалізованих у проблемних ділянках, зокрема повіках і зоні геніталій.…”
Section: місцева терапіяunclassified
“…Topical timolol has largely been shown to be effective in the treatment of infantile hemangiomas with a 96% response rate [4,9]; in addition, evidence is emerging for its use in other conditions including pyogenic granulomas, recalcitrant wounds, chronic ulcers, and portwine stains [10]. The mechanism of action of timolol is unclear but previous studies have shown that KS lesions are dependent on β-adrenergic signaling for the reactivation of HHV-8, resulting in proliferation of KS [11].…”
Section: Cks: Classic Kaposi's Sarcomamentioning
confidence: 99%